A Longitudinal Study of Resident Emotional Stability, Self-Reported Health and Perceptions of Programmatic Support - Franzen, Aaron B.; Doolittle, Benjamin R. (International Journal of Innovative Research in Medical Science, 2017)
Purpose: Certain characteristics such as acceptance, planning, and humility have correlated with less burnout among resident physicians. However, less is known about residency program culture, socialization, and support. The purpose of this study is to investigate social isolation, solidarity, stress, and frustration over time, their self-reported health, as well as the programmatic support. Methods: A longitudinal self-administered survey implemented within an academic pediatric residency program to track resident characteristics over time. Results: In Wave 1, among 101 residents, 78 (77%) responded. In Wave 2, among 98 residents, 73 (74%) responded. 45 residents were in both Wave 1 and 2. All measures of resident characteristics were stable over time. Worse overall health at Wave 2 is associated with feeling alone in residency at Wave 1 (r -.48). More stress (r .35), frustration (r .36) and feeling alone (r .53) (Wave 1) is associated with higher reports of bad mental health in Wave 2 while inversely associated with socializing frequently with other residents outside of work (r -.36) (Wave 1). Thinking the program helps residents cope with stress (r -.49) and that they communicate resources (r -.35) (Wave 1) correlate with improved mental health (Wave 2). Conclusion: Both negative characteristics such as stress and frustration as well as positive ones such as trust and socialization are stable over time. Some Wave 1 characteristics are healthful for residents while others deleterious at Wave 2. Perceptions of programmatic involvement may be helpful for resident mental health.